2021
DOI: 10.1002/nau.24705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prostatic radiation therapy on bladder contractility and innervation

Abstract: Aims: To determine the effect of prostatic radiation therapy (RT) on bladder contractility and morphology, and axon, or neuron profiles within the detrusor and major pelvic ganglia (MPG) in male rats. Methods: Male Sprague-Dawley rats (8 weeks) received a single dose of prostatic RT (0 or 22 Gy). Bladders and MPG were collected 2-and 10-weeks post-RT. Detrusor contractile responses to carbachol and electrical field stimulation (EFS) were measured. Bladders were stained with Masson's trichrome, and antibodies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The same could apply in our preparations since the CCH-induced maximal contraction strength was preserved, but the peak latency and maximal force change were significantly impaired. In contrast, the recent study by Turner et al [45] reported a KCl-induced decreased contraction of the bladder following irradiation of the rat prostate, and it was speculated that irradiation might also affect the smooth muscle itself. This highlights that the mechanisms of radiogenic injury to muscle remain poorly characterized.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The same could apply in our preparations since the CCH-induced maximal contraction strength was preserved, but the peak latency and maximal force change were significantly impaired. In contrast, the recent study by Turner et al [45] reported a KCl-induced decreased contraction of the bladder following irradiation of the rat prostate, and it was speculated that irradiation might also affect the smooth muscle itself. This highlights that the mechanisms of radiogenic injury to muscle remain poorly characterized.…”
Section: Discussionmentioning
confidence: 84%
“…This may indicate that MBI interfered with the signal transduction cascades of the contraction rather than the contractile apparatus itself, which would agree with the observations made in the current study on the esophagus. Similar physiologic studies were conducted with a rat urinary bladder [43][44][45] or with a human anal sphincter [46] using a conventional linear accelerator. Giglio et al [43] found that the methacholine and the electrical-field-stimulation (EFS) induced contractions were reduced after irradiation, whereas the contraction in response to potassium chloride (KCl) was not altered.…”
Section: Discussionmentioning
confidence: 92%
“…S1, I and J). To rule out persistent inflammation or altered detrusor function as alternative underlying causes of pain-like behavior and urinary frequency (47)(48)(49)(50), bladders were harvested from rUTI mice and assessed for immune infiltration by histology and flow cytometry (fig. S1, K to R) or detrusor function by muscle contractility assays (fig.…”
Section: Pelvic Sensitivity and Urinary Frequency After Ruti Are Asso...mentioning
confidence: 99%